(untitled) (Journal of Applied Learning and Teaching, 2021)
The purpose of this study was to examine the transformational leadership qualities of a young female academic in a Nigerian university through a qualitative descriptive technique. The study was grounded in the transformational leadership model of Bass (1990, 1997, 1999) and Bass and Avolio (1994) as the theoretical framework. Data were generated from the comments posted on the Facebook timeline of the young academic by her ex-students on her birthday. Obtaining data from Facebook users provide opportunities for qualitative research (Franz et al., 2019). The data were analysed using four themes based on the four components of transformational leadership proposed by Bass and Avolio which are idealized influence, inspirational motivation, intellectual stimulation and individualized consideration. The findings showed that the young academic demonstrates these four attributes or components in teaching and learning and in engagements with her students. The findings of the study underscore the need for academics to demonstrate transformational leadership, especially in Nigerian universities. The study also makes contribution to the current debate on transformational-instructor leadership.